Strategi Dakwah Interaktif Era Digital melalui Pemanfaatan Media Baru di Radio Irama FM - Wida Ulin Nuriyah; Akhmad Muhaini; Shofa Aulia Kumala (Hikmah, 2025)
This study examines how Radio Irama FM Purworejo builds an interactive da'wah strategy in the digital era by utilizing new media as a bridge closer to listeners. In the midst of changing information consumption patterns, radio is required not only to convey messages, but also to open a dialogue space that makes the audience feel heard and involved. Using qualitative descriptive methods through interviews, observations, and documentation, this study explores how broadcasters, creative teams, and listeners build more lively communication dynamics through social media, live streaming features, and two-way interaction based on digital messages. The results of the study show that a more humane da'wah approach that prioritizes proximity, warm language, and topics relevant to the daily lives of listeners has succeeded in increasing participation and expanding the reach of da'wah. These findings confirm that the adaptation of radio to digital technology is not only a technical need, but also an important means to present da'wah that is more touching, responsive, and in accordance with the character of today's audience.